Intergenerational mobility and self-selection of asylum seekers in Germany - Kolb, Michael; Neidhöfer, Guido; Pfeiffer, Friedhelm (Discussion paper, 2019)
We exploit a novel survey of recently arrived asylum seekers in Germany in order to estimate the degree of intergenerational mobility in education among refugees and compare it to the educational mobility of similar-aged individuals in their region of origin. The findings show that the refugees in our sample display high rates of educational mobility, and that their upward mobility is rather high when compared to the reference group in their region of origin. These results suggest that there exists positive skill selection among recently arrived refugees in Germany.